Protozoal meningoencephalitis and myelitis in 4 dogs associated with Trypanosoma cruzi infection. Issue 2 (March 2023) - Landsgaard, Kirsten A.; Milliron, Sarai M.; Faccin, Mayane; Broughton, Clark A; Auckland, Lisa D.; Edwards, John F.; Hamer, Sarah A.; Hensel, Martha E.
American trypanosomiasis is caused by the zoonotic protozoa Trypanosoma cruzi and primarily results in heart disease. Organisms also infect the central nervous system (CNS). The Texas A&M University veterinary teaching hospital archive was searched for dogs with CNS disease with intralesional protozoal amastigotes. This study summarizes 4 cases of dogs with disseminated trypanosomiasis and CNS involvement confirmed by quantitative polymerase chain reaction (qPCR) with T. cruzi primers. Clinical signs included lethargy, respiratory distress, tetraparesis, and seizures. Central nervous system lesions included meningeal congestion (1/4), necrosis with hemorrhage in the spinal cord gray and white matter (2/4), and histiocytic meningoencephalitis (4/4), and meningomyelitis (2/4) with intralesional and intracellular protozoal. Genotyping identified 1 case of T. cruzi discrete typing unit (DTU) TcI and 2 cases as TcIV, both are common variants in the United States. Trypanosomiasis should be considered a differential diagnosis for dogs with CNS signs in T. cruzi -endemic areas.